Analysis of Radiation Dose of Patients on CT Scan Examination using Si-INTAN Application - Siregar, Elshaday S.B; Sutapa, Gusti Ngurah; Sudarsana, I Wayan Balik (BULETIN FISIKA, 2020)
CT scan is widely used to diagnose the inside of the human body, so supervision is needed to ensure the health and safety of workers, patients and the public. One surveillance that can be done is to analyze the radiation dose of the patient on CT scan with the application of Si-INTAN. Data processing of the results of CT scan of the head, thorax and abdomen for ages 0-4 years, 5-14 years and ? 15 years using the Si-INTAN application. From the results of the data processing, the highest DRL DLP value and CTDI VOL values were obtained, for CT scan heads were 1732,8 mGycm and 31,92 mGy, the CT scan of the thorax was 2450,78 mGycm and 19,36 mGy, and for CT Abdominal Scans were 3968,85 mGycm and 19,35 mGy.